Real wages and monetary policy transmission in the euro area - Andrew McCallum; Frank Smets (Kiel Institute for the World Economy (IfW), 2007)
We use the Factor-Augmented Vector Autoregression (FAVAR) approach of Bernanke, Boivin and Eliasz (2005) to estimate the effects of monetary policy shocks on wages and employment in the euro area. The use of a large data set comprising country, sectoral and euro area-wide data allows us to better identify common monetary policy shocks in the euro area and their effects on labour market outcomes. At the same time the FAVAR approach gives us estimates of how relative wages and employment in the various countries and sectors respond to these common shocks. The ultimate objective of our work is to relate the estimated cross-country differences in wage and employment responses to differences in labour market institutions and sectoral composition.
Keywords: J3; E4; E3; J6; 330; VAR; factor models; rigidity; labour market